Delphinidin prevents high glucose-induced cell proliferation and collagen synthesis by inhibition of NOX-1 and mitochondrial superoxide in mesangial cells - Seung Eun Song; Hye Jun Jo; Yong-Woon Kim; Young-Je Cho; Jae-Ryong Kim; So-Young Park (Elsevier, 2016)
This study examined the effect of delphinidin on high glucose-induced cell proliferation and collagen synthesis in mesangial cells. Glucose dose-dependently (5.6-25 mM) increased cell proliferation and collagen I and IV mRNA levels, whereas pretreatment with delphinidin (50 μM) prevented cell proliferation and the increased collagen mRNA levels induced by high glucose (25 mM). High glucose increased reactive oxygen species (ROS) generation, and this was suppressed by pretreating delphinidin or the antioxidant N-acetyl cysteine. NADPH oxidase (NOX) 1 was upregulated by high glucose, but pretreatment with delphinidin abrogated this upregulation. Increased mitochondrial superoxide by 25 mM glucose was also suppressed by delphinidin. The NOX inhibitor apocynin and mitochondria-targeted antioxidant Mito TEMPO inhibited ROS generation and cell proliferation induced by high glucose. Phosphorylation of extracellular signal regulated kinase (ERK)1/2 was increased by high glucose, which was suppressed by delphinidin, apocynin or Mito TEMPO. Furthermore, PD98059 (an ERK1/2 inhibitor) prevented the high glucose-induced cell proliferation and increased collagen mRNA levels. Transforming growth factor (TGF)-β protein levels were elevated by high glucose, and pretreatment with delphinidin or PD98059 prevented this augmentation. These results suggest that delphinidin prevents high glucose-induced cell proliferation and collagen synthesis by inhibition of NOX-1 and mitochondrial superoxide in mesangial cells.